Persistent pain after breast cancer treatment - Smith, Howard S.; Wu, Sheng-Xi (Annals of Palliative Medicine; Vol 1, No 3 (October 04, 2012): Annals of Palliative Medicine, 2013)
Breast cancer is the commonest cancer affecting women with a 5-year survival over 80% as a result of earlier diagnosis and improved management. With improved survival rates, increasing attention is focused on the quality of life of these breast cancer survivors.